2021
DOI: 10.1111/jvim.16228
|View full text |Cite
|
Sign up to set email alerts
|

A dosing algorithm for individualized radioiodine treatment of cats with hyperthyroidism

Abstract: Background Radioiodine (131I) is the treatment of choice for hyperthyroidism in cats, but current 131I‐dosing protocols can induce iatrogenic hypothyroidism and expose azotemia. Objectives To develop a cat‐specific algorithm to calculate the lowest 131I dose to resolve hyperthyroidism, while minimizing risk of iatrogenic hypothyroidism and subsequent azotemia. Animals One thousand and four hundred hyperthyroid cats treated with 131I. Methods Prospective case series (before‐and‐after study). All cats had serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(76 citation statements)
references
References 49 publications
(151 reference statements)
5
66
0
5
Order By: Relevance
“…We recently published the results of a large cohort of hyperthyroid cats treated with individualized 131 I doses using a novel algorithm, calculated to administer the lowest effective dose possible. 7 With this dosing algorithm, we achieved euthyroidism at rates similar to previous studies using conventional dosing protocols (>95%), despite much lower 131 I doses, without increasing the probability of treatment failure (persistent hyperthyroidism). With this approach, the prevalence of overt hypothyroidism fell below 5%, but nearly 20% of 131 I‐treated cats still developed mild (subclinical) hypothyroidism.…”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…We recently published the results of a large cohort of hyperthyroid cats treated with individualized 131 I doses using a novel algorithm, calculated to administer the lowest effective dose possible. 7 With this dosing algorithm, we achieved euthyroidism at rates similar to previous studies using conventional dosing protocols (>95%), despite much lower 131 I doses, without increasing the probability of treatment failure (persistent hyperthyroidism). With this approach, the prevalence of overt hypothyroidism fell below 5%, but nearly 20% of 131 I‐treated cats still developed mild (subclinical) hypothyroidism.…”
Section: Introductionsupporting
confidence: 76%
“…The clinical details of the 1400 hyperthyroid cats in our study have been previously reported. 7 To be eligible for inclusion, cats underwent an evaluation that included a complete physical examination, routine laboratory testing (CBC, serum biochemical profile, complete urinalysis), determination of serum thyroid hormone concentrations (total thyroxine [T 4 ], triiodothyronine [T 3 ], and thyroid‐stimulating hormone [TSH]), 2 , 8 , 9 and qualitative and quantitative thyroid scintigraphy. 10 , 11 In the 728 cats treated with methimazole, owners discontinued administration of the drug ≥1 week (median, 7 days; interquartile range [IQR], 7‐15 days) before evaluation and treatment with 131 I.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations